Developing Standards for EFL in Indonesia as Part of the EFL Teaching Reform - Suwarsih Madya (TEFLIN, 2002)
Abstract: The teaching of English in Indonesia has so far been unable to reach its declared goal, which is the students mastery of the English macro skills listening, speaking, reading, writing. Various factors have certainly contributed to this failure, but the highly centralized curriculum has been one of the many to be blamed for it. The new system of regional autonomy gives ample opportunity to schools/ regions to develop their own curricula. This will lead to the need for the establishment of standard of English to ensure the achievement of the ultimate goal of teaching English throughout the country. This paper suggests that the development of standards for English should involve as many parties concerned as possible, including EFL teachers, EFL teacher educators, and users of school graduates. Another suggestion made related to the aspects to be covered in the standards, namely (1) the qualification of EFL policy makers, EFL teacher educators, and EFL teachers; (2) class size, (3) facilities and equipment, and (4) assessment and evaluation.